Determinantes da adoção de irrigação por citricultores da região centro-norte do Estado de São Paulo - Rossi, Fabiana Ribeiro (2017)
The orange activity of the State of Sao Paulo is very important for the Brazilian economy due mainly to job creation and for the expressive participation of the orange juice in national exports. In spite of the major growth and the economic stability faced by the Sao Paulo´s Citrus Agro industrial Complex during its consolidation in the mid-1980s, the last 25 years were marked by an economic environment very unfavorable to the orange growers, resulting in the loss of their profitability and the exodus of many producers from the orange production activity. One possible solution is a technological change in the orange orchards, leading to an increase in their productivity reducing the production costs per area. Thus, the producers’ incomes can raise or at least stabilize. Irrigation has been pointed out in the literature as an agricultural technology capable of providing several benefits to orange orchards, from the desired increase in productivity to improvements in fruit quality. However, this technology is still not widespread in the orange orchards of São Paulo. This thesis identify and analyse the determinants of the adoption of irrigation in the orange orchards of São Paulo, using a representative sample of 98 orange growers located in the center-north region of the state. The orange growers of the sample were interviewed using a semi-structured questionnaire and the primary data were analyzed by means of descriptive statistics, hypothesis test and double-hurdle econometric models. According to the results the participation in irrigation courses and in farmers associations, the higher soil fertility of the orange farms, the high dependence on the orange production activity, the use of sophisticated management tools and the access to rural credit affect positively and significantly the adoption of irrigation. On the other hand, the use of contracts in the sale of orange reduces the probability of adoption of irrigation in the orange orchards, since the orange farmers who irrigates sell their production, mostly, to the fresh fruit market through the use of spot market mechanism. Among the orange farmers who irrigates, those who use irrigation in a larger part of the orange area participate in irrigation courses, are very dependent on the orange activity, have a productive structure with less orange varieties, denser orchards, and properties with soils of low fertility. For these producers, the sale of the orange production is mainly done through the use of contracts with the processing industry. This mechanism can promote the necessary safety to intensify the use of irrigation in the properties.